EFEKTIFITAS PENGELOLAAN DANA SIMPAN PINJAM KELOMPOK KHUSUS PEREMPUAN (SPP) PADA UNIT PENGELOLAAN KEGIATAN PNPM DI KECAMATAN BUNTULIA KABUPATEN POHUWATO TAHUN 2011-2013 - Muhammad Anas (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aimed to describe the effectiveness of the management of funds Savings and Loan Special group Women (SPP) in units of PNPM Event Management In District Buntulia Pohuwato 2011-2013. The benefits of this research is to provide information about the effectiveness of the activities undertaken members of Savings and Loans Special Women in District Buntulia Pohuwato and provide information to those who need the information. Data collecting primary data and secondary data. Primary data obtained by distributing questionnaires to the respondents, while secondary data obtained from the institutions associated with the research. The method of sampling is done by